A COMPARATIVE STUDY OF VAMANA AND VIRECHANA IN MADHUMEHA W.S.R NIDDM TYPE-2 - Khedikar Neha L.; Karhade Mukund; Kubde Sneha (International Journal of Applied Ayurved Research, 2017)
Ayurveda advocates two kinds of treatment measures, namely Samshodhana and Samshamana. The vitiated doshas, which are eliminated from the Urdhwamarga i.e.by mouth is called Vamana, through Adhomarga (guda) is called Virechana. Vamana is indicated mainly for kapha dosha and kapholbana samsargaja or sannipataja doshas. Virechana is indicated for pitta dosha, pitta samsargaja doshas, kapha and vata doshas. Both Vamana and Virechana are the best treatment procedures for kledanashana, which is the key factor of prameha samprapti. In the modern system of medicine Madhumeha can be compared to Diabetes mellitus. In Ayurveda several treatment modalities are available to deal with the Madhumeha. Among these Vamana and Virechana have great importance in the treatment of Sthoola and Balawan Madhumehi.